Septic shock secondary to febrile urinary tract infection in a case of long-standing phimosis: A novel presentation (Indian Journal of Case Reports, 2024)
A case report of a 75-year-old Hindu, Indian old male presenting with septic shock and recurrent episodes of urinary tract infection (UTI). The patient had long-standing phimosis and balanitis for which emergency circumcision was done. This case illustrates how lack of education, poor personal hygiene, and access to basic surgical care for an easily treatable condition leads to advanced presentation of a severe disease process. The patient’s main concerns were recurrent UTI and the inability to retract the foreskin. The final diagnosis of urosepsis secondary to long-standing Phimosis was made. The patient was managed for urosepsis with intravenous antibiotics followed by circumcision. The patient had immediate relief of symptoms and urosepsis was managed well with no further episodes of UTI. This case illustrates how timely intervention could save a patient from life-threatening conditions such as urosepsis.